2006
DOI: 10.1063/1.2161193
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical calculations of CH4 and H2 associative desorption from Ni(111): Could subsurface hydrogen play an important role?

Abstract: The results of theoretical calculations of associative desorption of CH(4) and H(2) from the Ni(111) surface are presented. Both minimum-energy paths and classical dynamics trajectories were generated using density-functional theory to estimate the energy and atomic forces. In particular, the recombination of a subsurface H atom with adsorbed CH(3) (methyl) or H at the surface was studied. The calculations do not show any evidence for enhanced CH(4) formation as the H atom emerges from the subsurface site. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
140
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(152 citation statements)
references
References 39 publications
10
140
2
Order By: Relevance
“…0.66 eV for the tbe TS geometry, allowing surface relaxation) is in reasonably good agreement with the k-point converged value mentioned in ref. 19 (0.7 eV), and 0.27 eV smaller than the one reported by Qi et al 8 : 0.93 eV. The latter significant discrepancy might be partially due to the use of a 2×2 supercell in ref.…”
Section: Transition States For Ch3· · ·H Dissociationcontrasting
confidence: 51%
“…0.66 eV for the tbe TS geometry, allowing surface relaxation) is in reasonably good agreement with the k-point converged value mentioned in ref. 19 (0.7 eV), and 0.27 eV smaller than the one reported by Qi et al 8 : 0.93 eV. The latter significant discrepancy might be partially due to the use of a 2×2 supercell in ref.…”
Section: Transition States For Ch3· · ·H Dissociationcontrasting
confidence: 51%
“…For example, in the transition state for methane's dissociative chemisorption on Ni(111), [35][36][37][38][39][40] only one C-H bond is significantly extended, but the infrared-and Raman-active vibrations available for gas phase excitation are collective excitations of all four C-H oscillators. Isotopic substitution can change the identity of the molecule's normal mode vibrations and vibrational eigenstates, and is therefore a useful tool for expanding the range of vibrational motions available for probing transition state access.…”
Section: Resultsmentioning
confidence: 99%
“…The first Brillouin zone of the p(3 × 3) supercell is sampled with a 2 × 2 × 1 k -point mesh which is evidenced to be sufficient for such a large cell. [19] The energies of localized vibrations are substantial for light atoms such as H atoms. It is necessary to make zero-point energy (ZPE) correction to the adsorption energies and activation energy barriers.…”
Section: Computational Detailsmentioning
confidence: 99%
“…They found that the threefold hollow sites were also energetically favorable for the CH 2 adsorption, and the activation energy for the CH 3 dehydrogenation was calculated to be more than 1 eV. Ciobica and van santen [5] carried out ab initio calculations to study the CH x adsorption and methane dissociation on Ru (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). In their study, CH 2 appeared to be the most stable species on the surface and the energy barrier for CH 3 dissociation was 11 kJ/mol.…”
Section: Introductionmentioning
confidence: 99%